Thematic Evolution of Municipal Solid Waste Management Research - Khairul Hafezad Abdullah; Fadzli Shah Abd Aziz; Mohd Faizal Mohd Isa (Indonesian Journal of Environmental Management and Sustainability, 2021)
This study aims to learn the thematic evolution of Municipal Solid Waste Management research by revising Scopus indexed publications between 2001 and 2020. Within a longitudinal system, a scientific co-word inspection is conducted from 2001 to 2020. The publication series was split into two periods; the first period is from 2001 to 2010, and the second period is from 2011 to 2020. The findings, impact rates, and Municipal Solid Waste Management research’s conceptual growth are verified. In this emerging field of research, the co-word review established three key topic areas which are “Landfill”, “Urban Area”, and “Uncertainty”. The themes “Municipal Solid Waste,” “Waste Disposal,” “Costs,” “Waste to Energy” and “Environmental Impact Assessment” have changed from the first themes. The themes “Waste Management Systems,” “Treatment Technologies” and “Leachate” were found to have newly emerged and indicated that MSWM had been varied over successive periods. Future researchers could use this information to recognise the focus of awareness and make verdicts in various ways. There are a few limits of this study: 1) some of the Municipal Solid Waste Management publications may not have been included; 2) this study only considered publication records from the Scopus database, and 3) accordingly, the subject area may have changed if other new databases such as Google Scholar, Microsoft academics, or Dimensions have been retrieved. This study’s findings should be conceded as one proof-based structure for building future studies that benefit researchers, practitioners, and policymakers.